STUDENTS’ PERCEPTIONS OF PROJECT-BASED LEARNING (PJBL) IN P5 PROJECTS FOR ENHANCING WRITING SKILLS AT ISLAMIC BOARDING SCHOOL - Arifin, Syamsul; Anugerahwati, Mirjam; Suharyadi, Suharyadi (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2026)
This study aims to explore the perceptions of students toward Project-Based Learning (PjBL) in P5 projects for enhancing writing skills at Islamic Boarding Schools (IBS). It seeks to address key questions about students’ experiences, the impact of PjBL on writing development, the challenges encountered, and strategies for improvement. Adopting a convergent parallel mixed methods design, data were collected using an online questionnaire and semi-structured interviews. The questionnaire involved 84 students from As-Syifa Islamic Boarding School Sagalaherang Subang, while 12 participants, purposefully selected based on English proficiency (basic, intermediate, advanced) and willingness to participate, were interviewed for in-depth insights. Quantitative data were analyzed descriptively, and qualitative data were coded thematically. Findings reveal that PjBL in P5 projects positively influences students’ writing skills through real-world applications, collaborative tasks, and engaging activities. However, challenges such as time constraints, limited vocabulary, and group dynamics were noted. To enhance PjBL outcomes, students proposed extending time for writing tasks, providing immediate feedback, and integrating digital tools for autonomous learning support.